Early clinical and laboratory markers associated with post-COVID respiratory syndrome: A retrospective analysis - Yulia Ariani; Indra Gunawan; Agus Dwi Susanto; Riyadi Sutarto (PLoS ONE, 2026)
Background Post-COVID-19 respiratory syndrome remains a significant concern, yet early clinical and laboratory markers at the time of admission are not well established. Identifying laboratory markers associated with this condition could help guide clinical management and long-term monitoring. This study aimed to determine which laboratory findings at admission significantly differ between COVID-19 survivors with and without post-COVID respiratory syndrome (PCRS) and assess their potential as markers. Methods A retrospective comparative study was conducted on COVID-19 survivors who has history of hospitalization at Persahabatan National Referral General Hospital, Jakarta, in 2020–2021, divided into case (PCRS, n:43) and control (nonPCRS, n:42) groups. Demographic data, vital signs, and laboratory findings were analyzed, including complete blood count, kidney and liver function, electrolytes, blood gas analysis, D-dimer, and C-reactive protein (CRP). Results Compared with controls, cases demonstrated significantly higher neutrophil percentages, neutrophil-to-lymphocyte ratio (NLR), blood urea nitrogen (BUN), potassium levels, and respiratory rates, along with lower lymphocyte and eosinophil percentages at admission. After Benjamini–Hochberg correction for multiple testing, respiratory rate, potassium, BUN, and neutrophil percentage remained statistically significant. In adjusted multivariable logistic regression models controlling for age, sex, body mass index, and markers of disease severity (SpO₂ and/or respiratory rate), potassium and respiratory rate showed consistent independent associations with case status across several models, while NLR retained a modest association only in models incorporating SpO₂. No significant differences were observed for D-dimer or CRP. Conclusion Neutrophilia, lymphopenia, increased NLR, elevated BUN, potassium levels, and higher respiratory rates at admission were associated with post-COVID respiratory syndrome. Among these, potassium levels and respiratory rate showed more consistent associations after adjustment for demographic factors and disease severity markers. These findings describe admission characteristics linked to post-COVID-19 Respiratory syndrome. Larger prospective studies with serial measurements are needed to confirm their clinical relevance and prognostic value.